Pd Immobilization Phenanthroline-2,9-Dicarbaldehyde Modified Magnetic CuBDC MOF as a Reusable Heterogeneous Catalyst for Suzuki-Miyaura Cross-Coupling Reactions - Karimi-Nami, Rahman; Keypour, Hassan; Rabiei, Khadijeh; Kouhdareh, Jamal; Alavinia, Sedigheh; Karakaya, Idris (Taylor & Francis Ltd, 2024)
A porous magnetic multifunctional copper-based metal-organic framework (MOF) was developed through combined covalent and dative post-synthetic modification (PSM) of the CuBDC. In this regard, a novel magnetic metal-organic framework (MMOF) consisting of supported 1,10-phenanthroline-2,9-dicarbaldehyde (Fe3O4@Cu(BDC)-NH2-PHD) has been fabricated by post-synthetic modifications of Fe3O4@Cu(BDC)-NH2. Subsequently, the prepared nanocomposites were modified using palladium chloride ions (Fe3O4@Cu(BDC)-NH2-PdPHD) to impart catalytic sites. As a result, the fabricated magnetic porous catalyst exhibited great catalytic activity in Suzuki-Miyaura cross-coupling reactions. Some of the essential advantages of the synthesized catalyst are; high catalytic activity, short reaction times, mild conditions, high thermal stability, and reusability. Moreover, his porous magnetic nanomaterial can be used as a new support to immobilize other metals in different catalytic reactions.
Keywords: Metal-organic frameworks; Suzuki-Miyaura Cross-Coupling; C-C coupling; magnetic nano particles